PERSEPSI MAHASISWA D3 TATA BUSANA FAKULTAS PARIWISATA DAN PERHOTELAN UNIVERSITAS NEGERI PADANG UNTUK BERWIRAUSAHA - Yulandari, Cristya; Ernawati, Ernawati; Nelmira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study aims to determine students' perceptions of D3 dressmaking Faculty of Tourism and Hospitality University of Padang on entrepreneurship with a sample of 55 students of D3 dressmaking class of 2012 - 2014. The perception of entrepreneurship using three indicators: awareness, impact, and desire entrepreneurship. This research is quantitative descriptive by calculating the mean, median, mode, frequency distribution and classification techniques. Results of research students' perceptions D3 dressmaking for entrepreneurship in terms of awareness of entrepreneurship from 55 respondents 17 respondents are in the high category with a percentage (30.91%), Tourism and Hospitality in terms of impact of entrepreneurship 26 respondents at high category with a percentage (47.27%) and in terms of the desire for entrepreneurship 23 respondents at high category with a percentage (41.82%). It can be concluded that the D3 dressmaking student of the Faculty of University of Padang have the perception that high in terms of awareness, impact, and desire to entrepreneurship. Keywords: perception, entrepreneurship, awareness, impact, desire.